How do you evaluate (2x-3)(3x+2)?

2 Answers
Sep 22, 2017

6x^2-5x-6

Explanation:

You just have to expand it.

(2x-3)(3x+2)= (2x)(3x)-3(3x)+2(2x)+2(-3)=6x^2-9x+4x-6=6x^2-5x-6

And that's the answer!

Sep 22, 2017

6x^2-5x-6

Explanation:

"each term in the second bracket is multiplied by each"
"term in the first bracket"

(color(red)(2x-3))(3x+2)

=color(red)(2x)(3x+2)color(red)(-3)(3x+2)

=(color(red)(2x)xx3x)+(color(red)(2x)xx2)+(color(red)(-3)xx3x)+(color(red)(-3)xx2)

=6x^2+4x-9x-6

=6x^2-5x-6